Implementasi Manajemen Tata Usaha untuk Meningkatkan Kualitas Pelayanan Administrasi Madrasah - Zahrotun Ni’mah Afif; Ulil Albab Suamong (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2021)
This research aims to describe the implementation of administrative management in improving administrative services at MTs N 15 Jombang and identify supporting and inhibiting factors. The research uses qualitative methods with descriptive design. Data was collected through structured interviews, non-participant observation, and documentation, and analyzed using data reduction, data presentation, and verification techniques. The research results show that administrative management is carried out through planning, implementation, evaluation and follow-up which involves assigning tasks according to expertise and improving performance through communication and motivation. Supporting factors include appropriate assignment of tasks and a harmonious work environment while inhibiting factors include a mismatch between tasks and skills and a less professional attitude.